(untitled) (Web of Teachers: Inderscience Research, 2024)
This article examines the importance of electronics science today, the development of modern science and technology, as well as the development of electronics and nanotechnology. The importance and prospects of electronics science in teaching in higher educational institutions are also analyzed.